Kānl̄ưaktang, phak kānm̄ưang, læ sathīanraphāp kh̨ōng ratthabān - Kramol Tongdhamachart (Fāi Wičhai, Khana Ratthasāt, Čhulālongk̨ōnmahāwitthayālai, 1988)
Research on elections, political parties, and stability of government in Thailand.